The Impact of the Adoption of IAS.1 on Improving the Qualitative Characteristics Using Financial Indicators - An Applied study - عبد الحليم صفوان قصي; محمد منى جبار (Journal of Economics and Administrative Sciences, 2020)
The international financial accounting and reporting standards IFRS/IAS represent the set of rules and foundations that the economic entity must follow in the measurement, presentation, and disclosure of the elements of the financial statements, the implementation of adopting the international financial reporting standards contributes to improving the qualitative characteristics of accounting information, so the current research aims to explain the role of adopting the International Accounting Standard (IAS) in improving the qualitative characteristics as well as analyzing the impact of the adoption of IAS.1 in improving the qualitative characteristics of accounting information within the financial statements using the indicators of financial analysis for the Bank of Baghdad. The research reached a number of conclusions, the most important of which is the impact of the adoption of the International Accounting Standard (IAS.1) on the qualitative characteristics of accounting information for the financial statements of the Bank of Baghdad, and this appears clearly in the calculation of indicators of financial analysis. The most important recommendations were the necessity of requiring all local banks to adopt the International Accounting Standard (IAS.1) continuously according to internal and external variables, which will be reflected in the quality of accounting information and the need to use financial and non-financial indicators because of their impact in improving the quality of internal and external decisions.